Effects of Memantine on Aminoglycoside‐Induced Apoptosis of Spiral Ganglion Cells in Guinea Pigs. (29th March 2016) - Kim, Bo Young; Bae, Woo Yong; Hur, Dae Young; Kim, Jae‐Ryong; Koh, Tae Kyung; Lee, Tae Hoon; Park, Ga Bin
Abstract : Objective: To explore whether memantine, an N‐ methyl‐D‐aspartate receptor antagonist, exerts a neuroprotective effect against apoptosis of spiral ganglion cells (SGCs) induced by gentamicin. Study Design: An animal experiment. Setting: Dong‐A University College of Medicine, Busan, Korea. Subjects and Methods: Gentamicin was injected into the left cochleae of guinea pigs to induce apoptosis of SGCs; the contralateral cochleae served as controls. Memantine was intraperitoneally injected 12 hours and 1 hour prior to gentamicin injection. At 1 week after gentamicin and/or memantine injection, the cochleae were removed and stained with hematoxylin and eosin to evaluate morphologic changes and apoptosis. Western blotting was performed to measure FasL expression and the extent of caspase activation in SGCs. Results: SGC numbers remained stable after memantine treatment. Western blotting showed that FasL expression and activation of caspases 3, 8, and 9 were reduced in SGCs after memantine treatment. Conclusion: Memantine attenuated the gentamicin‐induced apoptosis of SGCs in guinea pigs. Moreover, memantine may affect Fas‐FasL signaling in the receptor‐mediated apoptotic pathway and caspase activation involved in the receptor‐mediated and mitochondrial apoptotic pathways.